Kompetensi Guru Pendidikan Agama Islam Pada Madrasah Aliyah Al-Urwatul Wutsqaa Benteng Sidrap - Sudirman (Jayapangus Press, 2020)
This research aims at evaluating the professional competence of Islamic education teachers and its correlation on student learning motivation Madrasah Aliyah Al-Urwatul Wutsqaa Benteng Sidrap. The respondents of this research are 10 teachers and 50 students of Madrasah Aliyah Al-Urwatul Wutsqaa Benteng Sidrap. This research reveals that the professional competence of teachers in Madrasah Aliyah PAI Al-Urwatul Wutsqaa Benteng Sidrap shows that the level of professional competence and motivation of student teachers in Madrasah Aliyah Al-Urwatul Wutsqaa Benteng Sidrap is on the high category. The further result discloses that there is a sufficient correlation and a significant influence between teacher competence and motivation of students.